TEACHER OF PRESCHOOL EDUCATION ORGANIZATION CREATIVE COMPETENCE IMPROVEMENT - Mamatmuminova Muxabbat Gaffarovna (Journals Park Publishing, 2022)
This in the article pedagogue educators creative potential increase, in them new thinking, creativity, innovation pedagogical from technologies effective use as well as tutor to be placed requirements, of the educator education in the process to training creative approach and trainees with together of cooperation to himself special aspects illuminated.
Keywords: pedagogue, creative potential, creativity,